Pengaruh Kepercayaan dan Harga terhadap Keputusan Pembelian dan Loyalitas Pelanggan pada pembelian Merchandise K-Pop melalui Group Order - Annisa Maulidia; Muhammad Fikry Aransyah (Universitas Batanghari, 2023)
Korean pop music or K-Pop is one of the Korean Wave products that millennials are interested in. During the pandemic era, K-Pop fans in Indonesia skyrocketed, leading to increased sales of K-Pop albums and other K-Pop merchandise. This study aims to determine the effect of trust and price on purchasing decisions and customer loyalty in purchasing merchandise K-Pop through Group Order. The research method used is descriptive quantitative. The population in this study are K-Pop fans who are members of the Group Order Jametal, while the samples obtained were 85 people. The sampling technique using the technique non probability sampling by method purposive sampling. Collecting data in this study used a questionnaire created through the Google form. Data was processed using IBM SPSS 25 software with validity and reliability test methods, classic assumption test, multiple linear regression test and hypothesis test (t test). The results of the study show that trust and price have a positive and significant effect on purchasing decisions. And trust and price have a positive and significant effect on customer loyalty.